Investment promotion in the new international context: What is the next frontier and how to get there - Fabrizio Opertti; Christian Volpe Martincus (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
This Perspective proposes a consistent set of evidence-based strategies to effectively promote FDI in the new, more uncertain global environment characterized by the digital transformation, the introduction of a rising number of policy interventions, the greater awareness of global supply chains' vulnerabilities, and the sustainability and inclusiveness imperatives.
Keywords: 330